Kinetic and structural roles for the surface in guiding SAS-6 self-assembly to direct centriole architecture - Banterle, Niccolò; Nievergelt, Adrian P.; Buhr, Svenja de; Hatzopoulos, Georgios N.; Brillard, Charlène; Andany, Santiago; Hübscher, Tania; Sorgenfrei, Frieda A.; Schwarz, Ulrich S.; Gräter, Frauke; Fantner, Georg E.; Gönczy, Pierre (Nature Communications, 2021)
Discovering mechanisms governing organelle assembly is a fundamental pursuit in biology. The centriole is an evolutionarily conserved organelle with a signature 9-fold symmetrical chiral arrangement of microtubules imparted onto the cilium it templates. The first structure in nascent centrioles is a cartwheel, which comprises stacked 9-fold symmetrical SAS-6 ring polymers emerging orthogonal to a surface surrounding each resident centriole. The mechanisms through which SAS-6 polymerization ensures centriole organelle architecture remain elusive. We deploy photothermally-actuated off-resonance tapping high-speed atomic force microscopy to decipher surface SAS-6 self-assembly mechanisms. We show that the surface shifts the reaction equilibrium by ~104 compared to solution. Moreover, coarse-grained molecular dynamics and atomic force microscopy reveal that the surface converts the inherent helical propensity of SAS-6 polymers into 9-fold rings with residual asymmetry, which may guide ring stacking and impart chiral features to centrioles and cilia. Overall, our work reveals fundamental design principles governing centriole assembly.
Gesehen am 10.03.2022